Quantitative ethnobotany and vulnerability of woody plant species in Nyé’été forest, South Region of Cameroon - Todou, Gilbert; Yves, Komo Mbarga; Tchobsala; Adamou, Ibrahima (Ethnobotany Research and Applications, 2023)
Background: Despite the importance of the wild plants, the degradation of ecosystems and plant populations increase noticeably due to climate change and anthropogenic pressure. Wrong methods of harvesting do not optimize foliar and fruit productions of the trees and even can kill them. This study focused on local usefulness and the vulnerability of wild woody plant species in Nyé’été forest in South-Cameroon. Methods: The methods of ethnobotanical inventories so called “walk-in-the-woods method” and "show and tell method" were applied to collect data. Main collected information concerned local names of useful plants, the harvested parts of the plants, the methods of harvesting and the different categories of use. Results: In total, 75 useful species divided into 66 genera and 31 families were reported. The richest families were Fabaceae (9 species in 9 genera), Apocynaceae (6 species in 6 genera), Annonaceae (6 species in 5 genera), Malvaceae (5 species in 3 genera) and Meliaceae (5 species in 4 genera). Seven main categories of use were recognized. Traditional medicine was the most important category (76% of inventoried species and VUT = 1329.96). Wood, bark, leaves and fruits were the most useful parts of plants because the response rate of each organ was Fki > 50 %. About 31 species were very vulnerable and 20 species were moderately vulnerable (Iv ≥ 2.5 and Iv 2 ≤ Iv < 2.5). According to IUCN status, 27 species were threatened of which Erythrophleum suaveolens was endangered species (EN). Conclusion: Obtained results would contribute effectively to appreciate the potentiality of useful plants of Cameroonian forests and the anthropogenic pressures to the plant resources in order to conserve them. Keywords: Ethnobotanical inventories, ethnobotanical potentialities, anthropogenic pressure, vulnerability, Cameroon